2015
DOI: 10.1245/s10434-015-4827-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Circumferential Resection Margin in Esophageal Cancer Patients After Neoadjuvant Chemoradiotherapy

Abstract: BackgroundCircumferential resection margins (CRM) for esophageal cancer (EC), defined by the College of American Pathologists (CAP; >0 mm) or the Royal College of Pathologists (RCP; >1 mm) as tumor-free (R0), are based on a surgery-alone approach. We evaluated the usefulness of both definitions in current practice with neoadjuvant chemoradiotherapy (nCRT).MethodsCRMs were measured in 209 patients (104 with nCRT) with locally advanced EC after transthoracic esophagectomy. Local recurrence and cancer related dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…They also found a lower heterogeneity of the comprised study in the analyzed CAP group as compared to the RCP group [11]. These results were supported in other recent retrospective studies [3,14,17,18]. A multicenter study comprising a total of 2,815 patients after esophagectomies found a reduced overall survival for patients with a positive CRM as compared to patients with tumor-free margins (17.1 vs. 28.0 months; p < 0.001) irrespective of the nodal status [3].…”
Section: Survivalsupporting
confidence: 74%
“…They also found a lower heterogeneity of the comprised study in the analyzed CAP group as compared to the RCP group [11]. These results were supported in other recent retrospective studies [3,14,17,18]. A multicenter study comprising a total of 2,815 patients after esophagectomies found a reduced overall survival for patients with a positive CRM as compared to patients with tumor-free margins (17.1 vs. 28.0 months; p < 0.001) irrespective of the nodal status [3].…”
Section: Survivalsupporting
confidence: 74%
“…The prognostic value of the oesophageal CRM has been demonstrated in many studies4 8, 10 11, 14, 15, 16 25, 26, 27, 28. A large multicentre study in 2016 9 demonstrated that the CAP definition of CRM positivity was independently predictive of poor survival, whereas a meta‐analysis29 suggested that, although the CAP definition identified the highest‐risk group, the RCP definition encompassed patients still at risk of poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…The College of American Pathologists (CAP) defines a positive CRM as tumour at the cut margin (TAM), which has been advocated in some studies4, 5, 6, 7, 8, 9, whereas the Royal College of Pathologists (RCP) defines a positive CRM as tumour within 1 mm, preferred in other studies10, 11, 12, 13. Some studies have found the CRM to be independently prognostically significant4 7, 9 10, 13, 14, 15, 16, and others have not5 6, 11 12, 17, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…Buckstein and colleagues [19] investigated the neoadjuvant radiation dose and short-and long-term outcomes in the National Cancer Database, 7325 patients with esophageal cancer receiving neoadjuvant CRT followed by curative surgery were identified and four radiation dose levels (40-41. 4 Gy, 45 Gy, 50.4 Gy, and 54 Gy) were assessed. After a median follow-up of 26.3 months, radiation dose level was not associated with differences in pCR (P = 0.21) or overall survival (P = 0.39).…”
Section: Discussionmentioning
confidence: 99%
“…R0 resection, pathological complete response (pCR) and downstaging have been regarded as strong and relevant predictors of increased survival in esophageal cancer patients who were undergoing neoadjuvant therapy [1,[4][5][6], nCRT shows the advantages of effective local therapy in combination with systemic treatment, and the benefits of the radiosensitising effect of chemotherapy compared with nCT. The recently published NeoRES trial in a mixed cohort of 181 patients with esophageal squamous cell carcinoma and adenocarcinoma of the distal esophagus, manifested that nCRT increases the pCR and R0 resection rates and decreases the proportion of patients with metastases in regional lymph nodes compared to nCT, though dose not significantly improve overall survival in squamous cell carcinoma patients [7].…”
Section: Introductionmentioning
confidence: 99%